Men who have sex with men diagnosed with a sexually transmitted infection are significantly more likely to engage in sexualised drug use. (January 2017) - Ottaway, Z; Finnerty, Fionnuala; Amlani, Aliza; Pinto-Sander, Nicolas; Szanyi, Joshua; Richardson, Daniel
The sexualised use of recreational drugs (Mephedrone, GBL/GHB, Crystal Meth) generally known as 'chemsex' in men who have sex with men (MSM) is thought to be associated with sexually transmitted infection (STI) acquisition; however there is little data showing a direct relationship. We reviewed 130 randomly selected cases of MSM with an STI attending our STI service and 130 controls (MSM attending the STI service who did not have an STI) between 5 May 2015 and 2 November 2015. Reported condomless anal sex was significantly higher in cases 90/121 (74%) compared with controls 65/122 (53%); ( χ 2  = 11.71, p  < 0.005, OR 2.54). Recreational drug use in the cases 38/122 (31%) was significantly greater than in controls 20/125 (16%); ( χ 2  = 7.88, p  < 0.005, OR 2.37). This demonstrates a link between STI acquisition and recreational drug use in MSM. Harm reduction initiatives identifying and addressing party drug use can help to improve the sexual health of MSM, including reducing risk-taking behaviours.